Genetically Modified Porcine Mesenchymal Stem Cells by Lentiviral Tbx18 Create a Biological Pacemaker - Yannan Hu; Ning Li; Liang Liu; Hao Zhang; Xiang Xue; Xin Shao; Yu Zhang; Xilong Lang (Hindawi Limited, 2019)
Background. Tbx18 is a vital transcription factor involved in embryonic sinoatrial node (SAN) formation process but is gradually vanished after birth. Myocardial injection of lentiviral Tbx18 converts cardiomyocytes into pacemaker-like cells morphologically and functionally. In this in vitro and in vivo study, genetical modification of porcine bone mesenchymal stem cells (BMSCs) by recapturing the Tbx18 expression creates a biological pacemaker which was examined. Methods. The isolated porcine BMSCs were transfected with lentiviral Tbx18, and the induced pacemaker-like cells were analyzed using real-time polymerase chain reaction and western blotting to investigate the efficiency of transformation. Then, the induced pacemaker-like cells were implanted into the right ventricle of the SAN dysfunction porcine model after the differentiation process. Biological pacemaker activity and ectopic pacing region were tested by an electrocardiograph (ECG) monitor. Results. The isolated porcine BMSCs expressed specific surface markers of stem cells; meanwhile, the expression of myocardial markers was upregulated significantly after lentiviral Tbx18 transfection. The porcine SAN dysfunction model was constructed by electrocoagulation using a surgical electrotome. The results showed that the mean heart beat (HR) of BMSCs-Tbx18 was significantly higher than that of BMSCs-GFP. An ectopic pacing region was affirmed into the right ventricle by ECG after implantation of BMSCs-Tbx18. Conclusion. It was verified that Lenti-Tbx18 is capable of transducing porcine BMSCs into pacemaker-like cells. Genetically modified porcine BMSCs by lentiviral Tbx18 could create a biological pacemaker. However, further researches in large-scale animals are required to rule out unexpected complications prior to application in clinical practice.